Accelerated degradation of tetrachloroethylene by Fe(II) activated persulfate process with hydroxylamine for enhancing Fe(II) regeneration. Issue 5 (27th May 2015) - Wu, Xiaoliang; Gu, Xiaogang; Lu, Shuguang; Qiu, Zhaofu; Sui, Qian; Zang, Xueke; Miao, Zhouwei; Xu, Minhui; Danish, Muhammad
Abstract: BACKGROUND: The addition of hydroxylamine (HA) could significantly moderate the accumulation of Fe(III) and accelerate the transformation from Fe(III) to Fe(II) and therefore improve the generation of the reactive oxygen species for tetrachloroethylene (PCE) contaminated groundwater remediation in Fe(II)‐activated persulfate (PS) systems. RESULTS: Results indicated that PCE could be completely degraded within 30 min in a PS/Fe(II)/HA system with PS/Fe(II)/HA/PCE molar ratio 30:4:20:1 at an initial PCE concentration of 0.15 mmol L −1 . A wider effective pH range and a much higher PCE degradation efficiency was achieved with the addition of HA, and optimal PCE removal was observed at an initial solution pH of 3.0, whereas a proper HA dosage was needed in practical applications since too low or too high HA concentrations adversely affected PCE removal. Moreover, radical scavenger experiments and probe compound tests clearly demonstrated that the primary reactive oxygen species generated in the PS/Fe(II)/HA process were OH, SO4 − and O2 − radicals. Study of the PCE degradation mechanism confirmed that PCE could be completely dechlorinated and that no volatile organic intermediate chlorinated products were detected in the PS/Fe(II)/HA system. CONCLUSION: This study provided a novel technique relying on a PS/Fe(II)/HA process for fast remediation of PCE‐contaminated groundwater. © 2015 Society of Chemical Industry